Dance lexicon in Shakespeare and his contemporaries : a corpus based approach - Caimbella, Fabio (New York: Routledge, 2021)
"This book provides a thorough analysis of terpsichorean lexis in Renaissance drama. Besides considering not only the Shakespearean canon, but also the Bard's contemporaries (e.g. dramatists as John Marston and Ben Jonson among the most refined Renaissance dance aficionados), the originality of this volume is highlighted in both its methodology and structure. As far as methods of analysis are concerned, corpora such as the VEP Early Modern Drama collection and EEBO, and corpus analysis tools such as #LancsBox, AntConc or the Sketch Engine software are used in order to offer the widest range of examples possible from early modern plays and provide co-textual references for each dance. Examples from Renaissance playwrights are fundamental for the analysis of connotative meanings of the dances listed and their performative, poetic and metaphoric role in sixteenth- and seventeenth-century drama. This study will be of great interest to Renaissance researchers, lexicographers and dance historians"--
Includes bibliographical references and index.
Keywords: Dance in literature; English drama; English drama; Renaissance -- England